Datasets:

Modalities:
Text
Languages:
English
Libraries:
Datasets
License:
proof-pile / formal /afp /Algebraic_VCs /Domain_Quantale.thy
Zhangir Azerbayev
squashed?
4365a98
raw
history blame
18.4 kB
(* Title: Domain Quantales
Author: Victor Gomes, Georg Struth
Maintainer: Victor Gomes <victor.gomes@cl.cam.ac.uk>
Georg Struth <g.struth@sheffield.ac.uk>
*)
section \<open>Component for Recursive Programs\<close>
theory Domain_Quantale
imports KAD.Modal_Kleene_Algebra
begin
text \<open>This component supports the verification and step-wise refinement of recursive programs
in a partial correctness setting.\<close>
notation
times (infixl "\<cdot>" 70) and
bot ("\<bottom>") and
top ("\<top>") and
inf (infixl "\<sqinter>" 65) and
sup (infixl "\<squnion>" 65)
subsection \<open>Lattice-Ordered Monoids with Domain\<close>
class bd_lattice_ordered_monoid = bounded_lattice + distrib_lattice + monoid_mult +
assumes left_distrib: "x \<cdot> (y \<squnion> z) = x \<cdot> y \<squnion> x \<cdot> z"
and right_distrib: "(x \<squnion> y) \<cdot> z = x \<cdot> z \<squnion> y \<cdot> z"
and bot_annil [simp]: "\<bottom> \<cdot> x = \<bottom>"
and bot_annir [simp]: "x \<cdot> \<bottom> = \<bottom>"
begin
sublocale semiring_one_zero "(\<squnion>)" "(\<cdot>)" "1" "bot"
by (standard, auto simp: sup.assoc sup.commute sup_left_commute left_distrib right_distrib sup_absorb1)
sublocale dioid_one_zero "(\<squnion>)" "(\<cdot>)" "1" bot "(\<le>)" "(<)"
by (standard, simp add: le_iff_sup, auto)
end
no_notation ads_d ("d")
and ars_r ("r")
and antirange_op ("ar _" [999] 1000)
class domain_bdlo_monoid = bd_lattice_ordered_monoid +
assumes rdv: "(z \<sqinter> x \<cdot> top) \<cdot> y = z \<cdot> y \<sqinter> x \<cdot> top"
begin
definition "d x = 1 \<sqinter> x \<cdot> \<top>"
sublocale ds: domain_semiring "(\<squnion>)" "(\<cdot>)" "1" "\<bottom>" "d" "(\<le>)" "(<)"
proof standard
fix x y
show "x \<squnion> d x \<cdot> x = d x \<cdot> x"
by (metis d_def inf_sup_absorb left_distrib mult_1_left mult_1_right rdv sup.absorb_iff1 sup.idem sup.left_commute top_greatest)
show "d (x \<cdot> d y) = d (x \<cdot> y)"
by (simp add: d_def inf_absorb2 rdv mult_assoc)
show "d x \<squnion> 1 = 1"
by (simp add: d_def sup.commute)
show "d bot = bot"
by (simp add: d_def inf.absorb1 inf.commute)
show "d (x \<squnion> y) = d x \<squnion> d y"
by (simp add: d_def inf_sup_distrib1)
qed
end
subsection\<open>Boolean Monoids with Domain\<close>
class boolean_monoid = boolean_algebra + monoid_mult +
assumes left_distrib': "x \<cdot> (y \<squnion> z) = x \<cdot> y \<squnion> x \<cdot> z"
and right_distrib': "(x \<squnion> y) \<cdot> z = x \<cdot> z \<squnion> y \<cdot> z"
and bot_annil' [simp]: "\<bottom> \<cdot> x = \<bottom>"
and bot_annir' [simp]: "x \<cdot> \<bottom> = \<bottom>"
begin
subclass bd_lattice_ordered_monoid
by (standard, simp_all add: left_distrib' right_distrib')
lemma inf_bot_iff_le: "x \<sqinter> y = \<bottom> \<longleftrightarrow> x \<le> -y"
by (metis le_iff_inf inf_sup_distrib1 inf_top_right sup_bot.left_neutral sup_compl_top compl_inf_bot inf.assoc inf_bot_right)
end
class domain_boolean_monoid = boolean_monoid +
assumes rdv': "(z \<sqinter> x \<cdot> \<top>) \<cdot> y = z \<cdot> y \<sqinter> x \<cdot> \<top>"
begin
sublocale dblo: domain_bdlo_monoid "1" "(\<cdot>)" "(\<sqinter>)" "(\<le>)" "(<)" "(\<squnion>)" "\<bottom>" "\<top>"
by (standard, simp add: rdv')
definition "a x = 1 \<sqinter> -(dblo.d x)"
lemma a_d_iff: "a x = 1 \<sqinter> -(x \<cdot> \<top>)"
by (clarsimp simp: a_def dblo.d_def inf_sup_distrib1)
lemma topr: "-(x \<cdot> \<top>) \<cdot> \<top> = -(x \<cdot> \<top>)"
proof (rule order.antisym)
show "-(x \<cdot> \<top>) \<le> -(x \<cdot> \<top>) \<cdot> \<top>"
by (metis mult_isol_var mult_oner order_refl top_greatest)
have "-(x \<cdot> \<top>) \<sqinter> (x \<cdot> \<top>) = \<bottom>"
by simp
hence "(-(x \<cdot> \<top>) \<sqinter> (x \<cdot> \<top>)) \<cdot> \<top> = \<bottom>"
by simp
hence "-(x \<cdot> \<top>) \<cdot> \<top> \<sqinter> (x \<cdot> \<top>) = \<bottom>"
by (metis rdv')
thus "-(x \<cdot> \<top>) \<cdot> \<top> \<le> -(x \<cdot> \<top>)"
by (simp add: inf_bot_iff_le)
qed
lemma dd_a: "dblo.d x = a (a x)"
by (metis a_d_iff dblo.d_def double_compl inf_top.left_neutral mult_1_left rdv' topr)
lemma ad_a [simp]: "a (dblo.d x) = a x"
by (simp add: a_def)
lemma da_a [simp]: "dblo.d (a x) = a x"
using ad_a dd_a by auto
lemma a1 [simp]: "a x \<cdot> x = \<bottom>"
proof -
have "a x \<cdot> x \<cdot> \<top> = \<bottom>"
by (metis a_d_iff inf_compl_bot mult_1_left rdv' topr)
then show ?thesis
by (metis (no_types) dblo.d_def dblo.ds.domain_very_strict inf_bot_right)
qed
lemma a2 [simp]: "a (x \<cdot> y) \<squnion> a (x \<cdot> a (a y)) = a (x \<cdot> a (a y))"
by (metis a_def dblo.ds.dsr2 dd_a sup.idem)
lemma a3 [simp]: "a (a x) \<squnion> a x = 1"
by (metis a_def da_a inf.commute sup.commute sup_compl_top sup_inf_absorb sup_inf_distrib1)
subclass domain_bdlo_monoid ..
text \<open>The next statement shows that every boolean monoid with domain is an antidomain semiring.
In this setting the domain operation has been defined explicitly.\<close>
sublocale ad: antidomain_semiring a "(\<squnion>)" "(\<cdot>)" "1" "\<bottom>" "(\<le>)" "(<)"
rewrites ad_eq: "ad.ads_d x = d x"
proof -
show "class.antidomain_semiring a (\<squnion>) (\<cdot>) 1 \<bottom> (\<le>) (<)"
by (standard, simp_all)
then interpret ad: antidomain_semiring a "(\<squnion>)" "(\<cdot>)" "1" "\<bottom>" "(\<le>)" "(<)" .
show "ad.ads_d x = d x"
by (simp add: ad.ads_d_def dd_a)
qed
end
subsection\<open>Boolean Monoids with Range\<close>
class range_boolean_monoid = boolean_monoid +
assumes ldv': "y \<cdot> (z \<sqinter> \<top> \<cdot> x) = y \<cdot> z \<sqinter> \<top> \<cdot> x"
begin
definition "r x = 1 \<sqinter> \<top> \<cdot> x"
definition "ar x = 1 \<sqinter> -(r x)"
lemma ar_r_iff: "ar x = 1 \<sqinter> -(\<top> \<cdot> x)"
by (simp add: ar_def inf_sup_distrib1 r_def)
lemma topl: "\<top>\<cdot>(-(\<top> \<cdot> x)) = -(\<top> \<cdot> x)"
proof (rule order.antisym)
show "\<top> \<cdot> - (\<top> \<cdot> x) \<le> - (\<top> \<cdot> x)"
by (metis bot_annir' compl_inf_bot inf_bot_iff_le ldv')
show "- (\<top> \<cdot> x) \<le> \<top> \<cdot> - (\<top> \<cdot> x)"
by (metis inf_le2 inf_top.right_neutral mult_1_left mult_isor)
qed
lemma r_ar: "r x = ar (ar x)"
by (metis ar_r_iff double_compl inf.commute inf_top.right_neutral ldv' mult_1_right r_def topl)
lemma ar_ar [simp]: "ar (r x) = ar x"
by (simp add: ar_def ldv' r_def)
lemma rar_ar [simp]: "r (ar x) = ar x"
using r_ar ar_ar by force
lemma ar1 [simp]: "x \<cdot> ar x = \<bottom>"
proof -
have "\<top> \<cdot> x \<cdot> ar x = \<bottom>"
by (metis ar_r_iff inf_compl_bot ldv' mult_oner topl)
then show ?thesis
by (metis inf_bot_iff_le inf_le2 inf_top.right_neutral mult_1_left mult_isor mult_oner topl)
qed
lemma ars: "r (r x \<cdot> y) = r (x \<cdot> y)"
by (metis inf.commute inf_top.right_neutral ldv' mult_oner mult_assoc r_def)
lemma ar2 [simp]: "ar (x \<cdot> y) \<squnion> ar (ar (ar x) \<cdot> y) = ar (ar (ar x) \<cdot> y)"
by (metis ar_def ars r_ar sup.idem)
lemma ar3 [simp]: "ar (ar x) \<squnion> ar x = 1 "
by (metis ar_def rar_ar inf.commute sup.commute sup_compl_top sup_inf_absorb sup_inf_distrib1)
sublocale ar: antirange_semiring "(\<squnion>)" "(\<cdot>)" "1" "\<bottom>" ar "(\<le>)" "(<)"
rewrites ar_eq: "ar.ars_r x = r x"
proof -
show "class.antirange_semiring (\<squnion>) (\<cdot>) 1 \<bottom> ar (\<le>) (<)"
by (standard, simp_all)
then interpret ar: antirange_semiring "(\<squnion>)" "(\<cdot>)" "1" "\<bottom>" ar "(\<le>)" "(<)" .
show "ar.ars_r x = r x"
by (simp add: ar.ars_r_def r_ar)
qed
end
subsection \<open>Quantales\<close>
text \<open>This part will eventually move into an AFP quantale entry.\<close>
class quantale = complete_lattice + monoid_mult +
assumes Sup_distr: "Sup X \<cdot> y = Sup {z. \<exists>x \<in> X. z = x \<cdot> y}"
and Sup_distl: "x \<cdot> Sup Y = Sup {z. \<exists>y \<in> Y. z = x \<cdot> y}"
begin
lemma bot_annil'' [simp]: "\<bottom> \<cdot> x = \<bottom>"
using Sup_distr[where X="{}"] by auto
lemma bot_annirr'' [simp]: "x \<cdot> \<bottom> = \<bottom>"
using Sup_distl[where Y="{}"] by auto
lemma sup_distl: "x \<cdot> (y \<squnion> z) = x \<cdot> y \<squnion> x \<cdot> z"
using Sup_distl[where Y="{y, z}"] by (fastforce intro!: Sup_eqI)
lemma sup_distr: "(x \<squnion> y) \<cdot> z = x \<cdot> z \<squnion> y \<cdot> z"
using Sup_distr[where X="{x, y}"] by (fastforce intro!: Sup_eqI)
sublocale semiring_one_zero "(\<squnion>)" "(\<cdot>)" "1" "\<bottom>"
by (standard, auto simp: sup.assoc sup.commute sup_left_commute sup_distl sup_distr)
sublocale dioid_one_zero "(\<squnion>)" "(\<cdot>)" "1" "\<bottom>" "(\<le>)" "(<)"
by (standard, simp add: le_iff_sup, auto)
lemma Sup_sup_pred: "x \<squnion> Sup{y. P y} = Sup{y. y = x \<or> P y}"
apply (rule order.antisym)
apply (simp add: Collect_mono Sup_subset_mono Sup_upper)
using Sup_least Sup_upper le_supI2 by fastforce
definition star :: "'a \<Rightarrow> 'a" where
"star x = (SUP i. x ^ i)"
lemma star_def_var1: "star x = Sup{y. \<exists>i. y = x ^ i}"
by (simp add: star_def full_SetCompr_eq)
lemma star_def_var2: "star x = Sup{x ^ i |i. True}"
by (simp add: star_def full_SetCompr_eq)
lemma star_unfoldl' [simp]: "1 \<squnion> x \<cdot> (star x) = star x"
proof -
have "1 \<squnion> x \<cdot> (star x) = x ^ 0 \<squnion> x \<cdot> Sup{y. \<exists>i. y = x ^ i}"
by (simp add: star_def_var1)
also have "... = x ^ 0 \<squnion> Sup{y. \<exists>i. y = x ^ (i + 1)}"
by (simp add: Sup_distl, metis)
also have "... = Sup{y. y = x ^ 0 \<or> (\<exists>i. y = x ^ (i + 1))}"
using Sup_sup_pred by simp
also have "... = Sup{y. \<exists>i. y = x ^ i}"
by (metis Suc_eq_plus1 power.power.power_Suc power.power_eq_if)
finally show ?thesis
by (simp add: star_def_var1)
qed
lemma star_unfoldr' [simp]: "1 \<squnion> (star x) \<cdot> x = star x"
proof -
have "1 \<squnion> (star x) \<cdot> x = x ^ 0 \<squnion> Sup{y. \<exists>i. y = x ^ i} \<cdot> x"
by (simp add: star_def_var1)
also have "... = x ^ 0 \<squnion> Sup{y. \<exists>i. y = x ^ i \<cdot> x}"
by (simp add: Sup_distr, metis)
also have "... = x ^ 0 \<squnion> Sup{y. \<exists>i. y = x ^ (i + 1)}"
using power_Suc2 by simp
also have "... = Sup{y. y = x ^ 0 \<or> (\<exists>i. y = x ^ (i + 1))}"
using Sup_sup_pred by simp
also have "... = Sup{y. \<exists>i. y = x ^ i}"
by (metis Suc_eq_plus1 power.power.power_Suc power.power_eq_if)
finally show ?thesis
by (simp add: star_def_var1)
qed
lemma (in dioid_one_zero) power_inductl: "z + x \<cdot> y \<le> y \<Longrightarrow> (x ^ n) \<cdot> z \<le> y"
proof (induct n)
case 0 show ?case
using "0.prems" by simp
case Suc thus ?case
by (simp, metis mult.assoc mult_isol order_trans)
qed
lemma (in dioid_one_zero) power_inductr: "z + y \<cdot> x \<le> y \<Longrightarrow> z \<cdot> (x ^ n) \<le> y"
proof (induct n)
case 0 show ?case
using "0.prems" by auto
case Suc
{
fix n
assume "z + y \<cdot> x \<le> y \<Longrightarrow> z \<cdot> x ^ n \<le> y"
and "z + y \<cdot> x \<le> y"
hence "z \<cdot> x ^ n \<le> y"
by simp
also have "z \<cdot> x ^ Suc n = z \<cdot> x \<cdot> x ^ n"
by (metis mult.assoc power_Suc)
moreover have "... = (z \<cdot> x ^ n) \<cdot> x"
by (metis mult.assoc power_commutes)
moreover have "... \<le> y \<cdot> x"
by (metis calculation(1) mult_isor)
moreover have "... \<le> y"
using \<open>z + y \<cdot> x \<le> y\<close> by simp
ultimately have "z \<cdot> x ^ Suc n \<le> y" by simp
}
thus ?case
by (metis Suc)
qed
lemma star_inductl': "z \<squnion> x \<cdot> y \<le> y \<Longrightarrow> (star x) \<cdot> z \<le> y"
proof -
assume "z \<squnion> x \<cdot> y \<le> y"
hence "\<forall>i. x ^ i \<cdot> z \<le> y"
by (simp add: power_inductl)
hence "Sup{w. \<exists>i. w = x ^ i \<cdot> z} \<le> y"
by (intro Sup_least, fast)
hence "Sup{w. \<exists>i. w = x ^ i} \<cdot> z \<le> y"
using Sup_distr Sup_le_iff by auto
thus "(star x) \<cdot> z \<le> y"
by (simp add: star_def_var1)
qed
lemma star_inductr': "z \<squnion> y \<cdot> x \<le> y \<Longrightarrow> z \<cdot> (star x) \<le> y"
proof -
assume "z \<squnion> y \<cdot> x \<le> y"
hence "\<forall>i. z \<cdot> x ^ i \<le> y"
by (simp add: power_inductr)
hence "Sup{w. \<exists>i. w = z \<cdot> x ^ i} \<le> y"
by (intro Sup_least, fast)
hence "z \<cdot> Sup{w. \<exists>i. w = x ^ i} \<le> y"
using Sup_distl Sup_le_iff by auto
thus "z \<cdot> (star x) \<le> y"
by (simp add: star_def_var1)
qed
sublocale ka: kleene_algebra "(\<squnion>)" "(\<cdot>)" "1" "\<bottom>" "(\<le>)" "(<)" star
by standard (simp_all add: star_inductl' star_inductr')
end
text \<open>Distributive quantales are often assumed to satisfy infinite distributivity laws between
joins and meets, but finite ones suffice for our purposes.\<close>
class distributive_quantale = quantale + distrib_lattice
begin
subclass bd_lattice_ordered_monoid
by (standard, simp_all add: distrib_left)
lemma "(1 \<sqinter> x \<cdot> \<top>) \<cdot> x = x"
(* nitpick [expect=genuine]*)
oops
end
subsection \<open>Domain Quantales\<close>
class domain_quantale = distributive_quantale +
assumes rdv'': "(z \<sqinter> x \<cdot> \<top>) \<cdot> y = z \<cdot> y \<sqinter> x \<cdot> \<top>"
begin
subclass domain_bdlo_monoid
by (standard, simp add: rdv'')
end
class range_quantale = distributive_quantale +
assumes ldv'': "y \<cdot> (z \<sqinter> \<top> \<cdot> x) = y \<cdot> z \<sqinter> \<top> \<cdot> x"
class boolean_quantale = quantale + complete_boolean_algebra
begin
subclass boolean_monoid
by (standard, simp_all add: sup_distl)
lemma "(1 \<sqinter> x \<cdot> \<top>) \<cdot> x = x"
(*nitpick[expect=genuine]*)
oops
lemma "(1 \<sqinter> -(x \<cdot> \<top>)) \<cdot> x = \<bottom>"
(*nitpick[expect=genuine]*)
oops
end
subsection\<open>Boolean Domain Quantales\<close>
class domain_boolean_quantale = domain_quantale + boolean_quantale
begin
subclass domain_boolean_monoid
by (standard, simp add: rdv'')
lemma fbox_eq: "ad.fbox x q = Sup{d p |p. d p \<cdot> x \<le> x \<cdot> d q}"
apply (rule Sup_eqI[symmetric])
apply clarsimp
using ad.fbox_demodalisation3 ad.fbox_simp apply auto[1]
apply clarsimp
by (metis ad.fbox_def ad.fbox_demodalisation3 ad.fbox_simp da_a eq_refl)
lemma fdia_eq: "ad.fdia x p = Inf{d q |q. x \<cdot> d p \<le> d q \<cdot> x}"
apply (rule Inf_eqI[symmetric])
apply clarsimp
using ds.fdemodalisation2 apply auto[1]
apply clarsimp
by (metis ad.fd_eq_fdia ad.fdia_def da_a double_compl ds.fdemodalisation2 inf_bot_iff_le inf_compl_bot)
text \<open>The specification statement can be defined explicitly.\<close>
definition R :: "'a \<Rightarrow> 'a \<Rightarrow> 'a" where
"R p q \<equiv> Sup{x. (d p) \<cdot> x \<le> x \<cdot> d q}"
lemma "x \<le> R p q \<Longrightarrow> d p \<le> ad.fbox x (d q)"
proof (simp add: R_def ad.kat_1_equiv ad.kat_2_equiv)
assume "x \<le> Sup{x. d p \<cdot> x \<cdot> a q = \<bottom>}"
hence "d p \<cdot> x \<cdot> a q \<le> d p \<cdot> Sup{x. d p \<cdot> x \<cdot> a q = \<bottom>} \<cdot> a q "
using mult_double_iso by blast
also have "... = Sup{d p \<cdot> x \<cdot> a q |x. d p \<cdot> x \<cdot> a q = \<bottom>}"
apply (subst Sup_distl)
apply (subst Sup_distr)
apply clarsimp
by metis
also have "... = \<bottom>"
by (auto simp: Sup_eqI)
finally show ?thesis
using ad.fbox_demodalisation3 ad.kat_3 ad.kat_4 le_bot by blast
qed
lemma "d p \<le> ad.fbox x (d q) \<Longrightarrow> x \<le> R p q"
apply (simp add: R_def)
apply (rule Sup_upper)
apply simp
using ad.fbox_demodalisation3 ad.fbox_simp apply auto[1]
done
end
subsection\<open>Relational Model of Boolean Domain Quantales\<close>
interpretation rel_dbq: domain_boolean_quantale
\<open>(-)\<close> uminus \<open>(\<inter>)\<close> \<open>(\<subseteq>)\<close> \<open>(\<subset>)\<close> \<open>(\<union>)\<close> \<open>{}\<close> UNIV \<open>\<Inter>\<close> \<open>\<Union>\<close> Id \<open>(O)\<close>
by standard auto
subsection\<open>Modal Boolean Quantales\<close>
class range_boolean_quantale = range_quantale + boolean_quantale
begin
subclass range_boolean_monoid
by (standard, simp add: ldv'')
lemma fbox_eq: "ar.bbox x (r q) = Sup{r p |p. x \<cdot> r p \<le> (r q) \<cdot> x}"
apply (rule Sup_eqI[symmetric])
apply clarsimp
using ar.ardual.fbox_demodalisation3 ar.ardual.fbox_simp apply auto[1]
apply clarsimp
by (metis ar.ardual.fbox_def ar.ardual.fbox_demodalisation3 eq_refl rar_ar)
lemma fdia_eq: "ar.bdia x (r p) = Inf{r q |q. (r p) \<cdot> x \<le> x \<cdot> r q}"
apply (rule Inf_eqI[symmetric])
apply clarsimp
using ar.ars_r_def ar.ardual.fdemodalisation22 ar.ardual.kat_3_equiv_opp ar.ardual.kat_4_equiv_opp apply auto[1]
apply clarsimp
using ar.bdia_def ar.ardual.ds.fdemodalisation2 r_ar by fastforce
end
class modal_boolean_quantale = domain_boolean_quantale + range_boolean_quantale +
assumes domrange' [simp]: "d (r x) = r x"
and rangedom' [simp]: "r (d x) = d x"
begin
sublocale mka: modal_kleene_algebra "(\<squnion>)" "(\<cdot>)" 1 \<bottom> "(\<le>)" "(<)" star a ar
by standard (simp_all add: ar_eq ad_eq)
end
no_notation fbox ("( |_] _)" [61,81] 82)
and antidomain_semiringl_class.fbox ("( |_] _)" [61,81] 82)
notation ad.fbox ("( |_] _)" [61,81] 82)
subsection \<open>Recursion Rule\<close>
lemma recursion: "mono (f :: 'a \<Rightarrow> 'a :: domain_boolean_quantale) \<Longrightarrow>
(\<And>x. d p \<le> |x] d q \<Longrightarrow> d p \<le> |f x] d q) \<Longrightarrow> d p \<le> |lfp f] d q"
apply (erule lfp_ordinal_induct [where f=f], simp)
by (auto simp: ad.addual.ardual.fbox_demodalisation3 Sup_distr Sup_distl intro: Sup_mono)
text \<open>We have already tested this rule in the context of test quantales~\cite{ArmstrongGS15}, which is based
on a formalisation of quantales that is currently not in the AFP. The two theories will be merged as
soon as the quantale is available in the AFP.\<close>
end